A Study of Betawi Architecture in Setu Babakan, Jakarta - Sudarwani, Margareta Maria; Widati, Galuh; G.S, Nousli Betna; Putri, Jessica (Semarang State University, 2021)
Abstract Betawi is one of the indigenous cultures that inhabit the capital city of Jakarta. This culture was born from a fusion of several cultures that came to the Jakarta area. Betawi culture can be seen from the system of customs that are still preserved such as silat, traditional food, community life, and traditional buildings that are still preserved today. This research used a case study of the Betawi cultural area located in Setu Babakan, Srengseng Sawah, South Jakarta. Setu Babakan area is a stronghold of the Betawi cultural heritage site which is still preserved today. The research objectives of the Betawi architectural concept in the Setu Babakan area are as follows: to know the Betawi architectural Concept, to identify the Betawi architectural concept in the Setu Babakan area, and to find solutions related to the application of Betawi architecture concept in architecture buildings today. The research method used a descriptive method based on empirical facts. The data of this research consisted of primary and secondary data obtained from literature and existing field conditions. Betawi culture as the local culture of the capital city of Jakarta is increasingly marginalized, it is even not the majority in its own area. The results of observations on the site of 879 housing units were divided into original houses as much as 22.75% characterized the Betawi architecture and 77.25% did not characterize Betawi architecture. The application of Betawi Architectural Ornaments in the Setu Babakan area, especially seen in the following elements: pendopo or front porch of the house, langkan [Betawi balustrades], hanging lamps, doors, windows, blinds, roofs, and colors.